Physics / Part 2: Third Edition - Halliday David; Resnick Robert J (John Wiley & Sons, 1977)
Charge and Matter, The Electric Field, Gauss's Law, Electric Potential, Capacitors and Dielectrics, Current and Resistance, The Magnetic Field, Ampere's Law, Faraday's Law of Induction, Inductance, Magnetic Properties of Matter, Electromagnetic Oscillations, Alternating Currents, Maxwell's Equations, Electromagnetic Waves, The Nature and Propagation of Light, Reflection and Refraction - Plane Waves and Plane Surfaces, Reflection and Refraction - Spherical Waves and Spherical Surfaces, Interference, Diffraction, Gratings and Spectra, Polarization, Light and Quantum Physics, Waves and Particles, Supplementary Topics, Appendices, Index.